Magnetic resonance imaging T2* of the pancreas value using an online software tool and correlate with T2* value of myocardium and liver among patients with transfusion-dependent thalassemia major - Hoe, Han Guan; Git, Kim-Ann; Loh, C-Khai; Abdul Latiff, Zarina; Hong, Joyce; Abdul Hamid, Hamzaini; Wan Sulaiman, Wan Noor Afzan; Mohd Zaki, Faizah (Frontiers in Radiology, 2022)
Objective Patients with thalassemia major do require lifetime blood transfusions that eventually result in iron accumulation in different organs. We described the usefulness of using magnetic resonance imaging (MRI) T2*imaging values for the evaluation of pancreatic iron load in these patients, and we correlated it with MRI T2* haemosiderosis of the myocardium and liver that has been recognized as a non-invasive assessment of iron overload among patients with thalassemia major. Materials and methods We conducted a cross-sectional study on 39 patients with thalassemia major in one of the tertiary university hospitals for a 1-year period. Demographic data were collected from the patient's history. MRI T2* of the pancreas, liver, and heart were executed on all patients in the same setting. Objective values of iron overload in these organs were obtained using the MRI post-processing software from online software. Results A total of 32 (82.1%) patients had pancreatic iron overload including 2 patients (5.1%) with severe iron overload and 15 patients (38.5%) with moderate and mild iron overload, respectively. Nine patients (23.1%) had myocardial iron overload, which included 3 patients (7.7%) who had severe cardiac haemosiderosis. Notably, 37 patients (94.9%) had liver iron overload, which included 15 patients (38.5%) who had severe liver haemosiderosis. There was a moderate positive correlation between the relaxation time of the pancreas and heart haemosiderosis (r = 0.504, P < 0.001). No significant correlation was found between the relaxation time of the pancreas with the liver and the heart with the liver. Conclusion Pancreatic haemosiderosis precedes cardiac haemosiderosis, which establishes a basis for initiating earlier iron chelation therapy to patients with thalassemia major.